LIPOSOMAL DELIVERY OF IMMUNOMODULATORY ANTIGEN OF B. MALAYI: ISOLATION, PREPARATION, CHARACTERIZATION, AND IMMUNE RESPONSES ASSESSMENT - Jain, Neeraj; Jain, Neelam (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study was aimed on developing and characterizing liposomal delivery system loaded with antigen of filaria parasite Brugia malayi extracted protein for assessment of humoral immune responses of antigen. Methods: Liposomes were prepared by reverse-phase evaporation method with slight modification using molar ratio of Soya PC: PE:Cholesterol in different molar concentrations. Results: The levels of F6 specific immunoglobulin (Ig) G1, IgG2a and IgG2b antibodies were found to be elevated in immunized animals over non-immunized controls. Analysis of IgG-subclasses revealed that all the subclasses at (1:25dilution) increased several folds over the controls with IgG1 showing the greatest increase (25.0-fold) followed by IgG2b (3.0-fold). Antibodies titers showed the many fold increment of titers on liposomized antigen groups (Gr.I; without booster dose and Gr.IV; with booster dose). IgG showed about 2.2 fold increment in Gr.IV than control group (Gr.V). IgG1 after booster dose showed about 25-fold increment followed by IgG2b than IgG2a. Conclusion: These results suggest that the liposomal antigen delivery system shows 25-fold IG-G responses in comparison to plain administrated antigen.